Assertive Communication Training to The Wives of Fisherman As A Social Support to Reduce Father Smoking Intensity in The House - Nurul Haniza (Sekolah Tinggi Manajemen IPMI, 2021)
Children who are exposed to secondhand smoke from their parents are more at risk of suffering fromvascular and heart health problems in the future, besides that smoking behavior in fathers also causeslow nutritional status in smokers' families. Stopping smoking is very difficult, so smoking away fromchildren is one solution that can be offered to keep children from being exposed to cigarette smoke butfathers can still smoke through a process of communication between partners. The purpose of the studywas to determine the effectiveness of wife assertive communication as a form of social support for thefather's smoking behavior outside the home. The research conducted was research with intervention inthe form of assertive communication training on wives. The location of the study was conducted in theFisherman Village in Bulukumba District, South Sulawesi. Therefore communication in an assertive wayis considered important to do so that the father also does not feel disturbed "pleasure" when smoking.The sample is the wife of the fishermen who will be given assertive knowledge or techniques totaling 26people. The wife was chosen to be the target of intervention because the female partner would moreeasily influence his male partner in changing his negative behavior. All statistical tests on the pre-testand post-test assertive communication training, and pre-test and post-test intense daddy smokingoutside the home were conducted with non-parametric test methods taking into account the number ofsamples n = <30. % of the significance assumption of 5%. The results of the study conducted showedthat assertive communication given to fishermen's wives had not provided the ability for mothers toassert communication with their fathers to reduce smoking at home. ((Mdn = 24.50) in the pre-test and(Mdn = 23.50) in the post-test, in the post-test, ɀ = -0.446, p <0.5; r = -0.152). This is because thelanguage of the material uses the language of "science" which is not understood because of the loweducation of the fishermen and the fairly short intervention time. The conclusion of the study showedthat there was no increase in changes in assertive communication skills in the intervention subjects(mothers) after being given treatment or assertive communication training interventions. In terms ofknowledge, the intervention subject gets a better understanding, but the skills or skills to makecommunication are still inadequate. Nevertheless, the social control function of the family in terms ofchanging smoking behavior must be fixed and continuously improved by providing the ability to "dare"to provide health information to their partners. Suggestion: Assertive communication training needs tobe followed up by health workers to limit the smoking behavior of fathers in the home which are alsogiven to health cadres and empowerment workers in the village, which is supported by the causes ofmedia coverage for health communication.Keywords: Assertive communication, social support, smoking behavior